Design and Manufacturing of Anemometer for Hot Gases from available ‎Cheap Materials (Journal of University of Babylon for Engineering Sciences, 2022)
This work is to build anemometer, especially for hot air or hot gas flow, from a very cheap materials available as a waste in reforming shops and small factories. The design of this tool takes in to account that any primitive technician or smith can build the tool.  At the beginning, the parts of tool are designed using Catia V5R17 Software and some parts are imported to ANSYS WORKBENCH 2020 R2 software for test of mechanical stresses and deformation associated with temperature increment. Then, theoretical computations are made where angular displacement is calculated, based on equations solved by MATLAB R2020a software, where the tool faces flow air streams with different speed magnitudes. Those different air speed magnitudes used in the experiment are 1 m/s, 1.5 m/s, 2 m/s, 2.5 m/s, 3 m/s, 3.5 m/s, and 4 m/s. After that, a real tool is built and be placed in duct having a dimensions of 2 m length, 0.35m height and 0.3m width. The air flowing in that duct has the same different speed magnitudes used in theoretical computations. Then, comparison between the two results is made, which show that despite there is a relatively slide difference in angular displacement readings but the response of the real tool to the different air speed magnitudes are very coincides with the theoretical.